Pengaruh Atribut Produk dan Persepsi Harga terhadap Keputusan Pembelian di Toko Sinar Elektronik Majene - Dewi, Ratna; Syamrul, Syamrul; Astuti, Sri; Utami, Mega; Faisal, Faisal; Saharuddin, Saharuddin; Ratna, Dewi (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to analyze the effect of product attributes and price perception on purchasing decisions of electronic products at Toko Sinar, Majene Regency. The study uses a quantitative approach with a survey method. The respondents consist of 51 consumers selected using accidental sampling. Data were collected through questionnaires with a Likert scale. The data were analyzed using validity tests, reliability tests, multiple linear regression analysis, and t-tests with the support of SPSS software. The results show that product attributes have a significant effect on purchasing decisions. Price perception also has a significant effect on purchasing decisions of electronic products. Simultaneously, product attributes and price perception have a significant influence on consumer purchasing decisions. These findings indicate that consumers consider product quality, features, design, and price suitability with perceived benefits before making a purchase. This study provides practical implications for Toko Sinar to improve competitiveness by optimizing product attributes and setting prices that match consumer expectations.